Design of an innovative nanovehicle to enhance brain permeability of a novel 5-HT6 receptor antagonist - María Javiera Alvarez-Figueroa; Francisco Nuñez-Navarro; Gonzalo Recabarren-Gajardo; José Vicente González-Aramundiz (Elsevier, 2024)
An innovative nanovehicle based on lipid nanocapsules (LNC) was designed to facilitate the passage of a new 5-HT6 receptor antagonist, namely PUC-10, through the blood-brain barrier. PUC-10 is a new synthetic N-arylsulfonylindole that has demonstrated potent 5-HT6 receptor antagonist activity, but it exhibits poor solubility in water, which indicates limited absorption. The lipid nanocapsules designed had a nanometric size (53 nm), a monomodal distribution (PI<0.2), a negative Z potential (−17 ± 7 mV) and allowed efficient PUC-10 encapsulation (74 %). Furthermore, the LNC demonstrated to be stable for at least 4 weeks at 4 °C (storage conditions), for at least 4 h in DMEM at pH 7.4, and for 18 h in water with 5 % DMSO, with both latter conditions maintained at 37 °C. They also demonstrated that cell viability was not affected at the different concentrations studied. Finally, in vitro studies that simulate the blood brain barrier (PAMPA-BBB) demonstrated that the nanoencapsulation of PUC-10 promoted their penetration through the blood-brain barrier, with a calculated permeability of 1.3 × 10−8 cm/s, compared to the null permeability exhibited by non-nanoencapsulated PUC-10.